PENERAPAN PENDEKATAN PMRI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VC SD NEGERI 42 PEKANBARU - Yanti, Oktaria Tri; Witri, Gustimal; ', Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the lack of students' mathematics learning outcomes, it is seen from the average value of students is 66.57. Of the 38 students, who reached the KKM (Minimum Criteria for completeness) only 23 students (60.52%) while those not reached KKM as many as 15 students (39.48%) with a predetermined value KKM is 71. The aim of this study is to improve mathematics learning outcomes VC grade students of SD Negeri 42 Pekanbaru through PMRI approach by the number of students 42 people, 30 male students and 12 female students. Research design used is Action Research (PTK) by 2 cycles, each cycle consisting of twice-face and one daily tests. Once applied the approach PMRI seen an increase in the percentage of teachers in the first cycle of activity that is 59.37% increased in the second cycle into 78.12%. The percentage of student activity also increased from the first cycle that 59.37% to 71.87 in the second cycle. The average value of students has increased from a base score 66.57 into 77.22 in the first cycle and became 81.14 in the second cycle. Learning outcome from a base score to the first cycle that 15.99% and from a base score to the second cycle is 21.88%. The percentage of classical completeness on a base score 60.52% increase in the first cycle to 76.19% and increased again in the second cycle into 84.61%. Based on the above data it is known that through the aplication approach PMRI can improve math learning outcomes class VC SD Negeri 42 Pekanbaru.Keywords: Approach PMRI, Math Learning Outcomes